Supply chain management open innovation: Virtual integration in the network logistics system - Vladimir Ščerbakov; Galina Silkina (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The customer-oriented approach is actively developing within the global trend of the modern industrial revolution that is Industry 4.0. The focus on customer interests has led to cooperation and integration in supply chains, improving their efficiency and increasing transparency, awareness, and trust. However, an issue emerging in this scenario is that conventional supply chain management (SCM) procedures are unable to identify the potential proposal for a particular user. Modern businesses need to build integrated supply chains, which require well-developed infrastructure and easily available complementary services, relying on logistics as a networking technology. Supply chains of this generation grow from traditional individual desynchronized economic relations (linear models with some feedback and the simplest network configurations) to scalable, adaptable, harmonized partner networks. The logistics potential allows additional income by reducing the total costs of participants in the network, thus increasing the competitiveness of companies; this can be implemented based on new models of interaction in the current digital environment through, firstly, system integration. Our goal consists of identifying the essential characteristics of system integration and substantiating the methods for its implementation in the digital economy. The study is based on the analysis of global best practices, considering the reports from leading consulting companies and competent analytical agencies. We have confirmed that the role of a virtual system integrator of supply chains belongs to logistics platforms; the effects of a transition to platform business models are discussed in detail.
Keywords: 650; digital logistics platform; digitalization tools; open innovation; supply chain management; supply chain networks